Perception and knowledge of high school students about science popularization in schools supported by PIBID - Gheler-Costa, Carla [UNESP]; Antoniassi, Beatriz [UNESP]; Siqueira, Marcos Vinicius Bohrer Monteiro (Fronteiras: Journal of Social, Technological and Environmental Science, 2021)
The contribution of the Institutional Scholarship Program for Initiation to Teaching (PIBID) in the training of future teachers and in the improvement of the teaching of the schools that are included in the program is indisputable. However, few reports whether this integration between higher education and basic education popularizes science and awakens students to research, because the reports are mostly about the promotion of events linked to the projects and the perception of the PIBID scholarship students. This work investigated the perception of high school students about the popularization of science in two state schools, one being contemplated with the PIBID program and another not. The data were collected through questionnaires applied to high school students and were compared with the participation rate of these students in a science fair whose main objective is to popularize science. The results show that the students of the PIBID schools understand the popularization of science and that there is an increasing interest in the participation of these students in popularizing events such as science fairs. In this way it was verified that the presence of PIBID in schools is capable of uniting teaching and research, thus contributing to an integrated and quality education.
Percepção e conhecimento de estudantes do ensino médio sobre popularização da ciência em escolas apoiadas pelo PIBID
Keywords: Formative educational experiences; Popularization of Science; Teaching; Teaching strategies